Establishing a Sound Credit Reporting System: Perspective from Doing Business - Jiang, Nan (International Finance Corporation, Washington, DC, 2014)
Credit registries and bureaus essential elements of the financial infrastructure enhance access to financial services. By sharing credit information, they help reduce information asymmetries, increase access to credit for small firms, improve borrower discipline, and support bank supervision and credit risk monitoring. This SmartLesson focuses on the Doing Business Getting Credit Credit Information index, which measures rules and practices affecting the coverage, scope, and accessibility of credit information available through a credit registry or bureau.